PENGARUH MODEL INKUIRI UNTUK MENINGKATKAN KETERAMPILAN ARGUMENTASI PESERTA DIDIK TERHADAP MATERI GETARAN DAN GELOMBANG - Sandhy, Afifah Kurnia; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis paper determined the effect of inquiry learning model to improve students' argumentation skills on the vibration and wave materials. This research was a pre-experimental design with one-group pretest-posttest design. This research was conducted at SMP Negeri 3 Pontianak in class VIII D with 39 students. The research data were collected using the test of 6 essay questions based on the indicator of the argumentation skills according to Toulmin. The average of students' argumentation skill during pretest was 17,79 and the average of posttest was 34,05, then the N gain was 0,44 with the medium category. The result showed that the data was normal and homogeneous so that the t test was done with the significance level of 5% and there was a significant improvement of the students' argumentation skill after inquiry model on vibration and wave material was applied. The implementation of the inquiry model during the learning process had a percentage of 93,75% with the â€œvery goodâ€ category and the response of the studentsâ€™ showed the persentage of 80,28% with the â€œgoodâ€ category. The results of this study were expected to be an alternative to improve the studentsâ€™ argumentation skills on the vibration and wave materials.Â Keywords: Argumentation skill, Inquiry, Vibration and Waves